A Behavioural Measure of Imagination Based on Conceptual Combination Theory. Issue 4 (2nd October 2021) - Horng, Ruey-Yun; Wang, Ching-Wen; Yen, Yung-Chieh; Lu, Chia-Ying; Li, Chien-Tao
ABSTRACT: Conceptual combination is proposed as the mental activity by which imagination produces new ideas in creative processes. Two parallel forms of the imagination test were constructed based on conceptual combination theory. Each test comprises eighteen unrelated noun-noun pairs. For each pair, an original idea is required. The test-retest reliability and the predictive validity of these two parallel forms of imagination test were examined. The originality of the imagination was found to predict design students' performance in design projects. However, the originality of one's imagination had little relation to either divergent thinking ability or creative personality. Imagination appears to be a psychological construct distinct from divergent thinking ability and may serve as an alternative behavioral measure of creative potential. Imagination, as defined by a mental act of conceptual combination, may serve as an explanation for what happens in the incubation stage and how the "aha" experience is produced.